Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Learning-guided cross-sampling for large-scale evolutionary multi-objective optimization - Haofan Wang; Li Chen; Xingxing Hao; Rong Qu; Wei Zhou; Dekui Wang; Wei Liu (Swarm and Evolutionary Computation, 2024)

Contribution, absorption mode, and model prediction of atmospheric deposition to copper and lead accumulation in soybean - Min Li; Haotian Wang; Ziqi Chen; Hailong Liu; Huan Zhao; Xiuting Rong; Ruizhi Xia; Xiaozhi Wang; Jun Zhou (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Nitrate Over Ammonium: Limited inorganic N niche partitioning between wheat and weeds regardless of fertilization treatment - Peilin Han; Yizhong Rong; Weiqiang Liu; Jie Liu; Li Zhang (Rhizosphere, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

Physio-mechanical properties of loess-paleosol sequences over the past 400 ka and their paleoclimate controlling factors on the central Loess Plateau - Xiaoning Wang; Dapeng Yue; Jingbo Zhao; Lixing Zhang; Rong Liu; Jianing Li; Yueshan Liu (Quaternary Science Reviews, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Experimental study of interception effect by submerged dam on microplastics - Jianhao Jiang; Lulu He; Junping Liu; Xu Liu; Junbao Huang; Li Rong (Journal of Hazardous Materials, 2024)

Secondary activation on plasma-activated water by plasma-treated cotton for restoring and enhancing disinfection effect - Zifeng Wang; Shenghang Xu; Xiangyu Wang; Dingxin Liu; Wanchun Li; Rusen Zhou; Qiuyi Yue; Pengfei Zhang; Jishen Zhang; Hao Zhang; Li Guo; Dandan Pei; et al. (Journal of Hazardous Materials, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Responses of yield, CH4 and N2O emissions to ratoon rice cropping and different management practices - Haiyang Yu; Rong Zhu; Xuechen Zhang; Xiangtian Meng; Chao Kong; Guangbin Zhang; Xinhui Liu; Yaying Li; Yongxiang Yu; Huaiying Yao (Field Crops Research, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Block copolymer nanoparticles doping polyacrylonitrile membranes for efficient adsorption of water-soluble dyes from water - Rong Cao; Enyang Zhang; Yuan Liu; Axiang Li; Wangqing Zhang (Chemical Engineering Journal, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Soil nutrient levels are associated with suppression of banana Fusarium wilt disease - Yifan Cao; Yannan Ou; Nana Lv; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Soil Ecology Letters, 2024)

Unraveling fertilization effects on the dynamics of arbuscular mycorrhizal fungal community in the Qinghai-Tibet Alpine Meadow - Longfei Liu; Yi Ren; Shuo Sun; Chen Liu; Kairui Ding; Rong Li; Pengfei Zhang; Biao Shen; Mohammadhossein Ravanbakhsh; Wu Xiong; Qirong Shen (Soil Ecology Letters, 2024)

Nitrifying and denitrifying microbes exhibit distinct community structure and activity responses to different crop rotation systems in subtropical paddy soils - Huifang Xu; Ke Li; Rong Sheng; Hongling Qin; Yi Liu; Anlei Chen; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Applied Soil Ecology, 2024)

Preparation of amino-functionalized CoAl-LDH/palygorskite hierarchical composites for CO2 capture - Shixiang Zuo; Min Sun; Weifeng Gong; Tongtong Tang; Xuhua Ye; Wenjie Liu; Ngie Hing Wong; Rong Xu; Guihua Chen; Chao Yao; Haoguan Gui; Xiazhang Li (Applied Clay Science, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Promotion of aromatic amino acids of extracellular polymeric substance targeted transformation via sulfite mediated iron redox cycling in sludge solid-liquid separation - Jiahao Lai; Huan Liu; Zhen Yang; Rong Deng; Yun Xiong; Yafei Li; Min Song (Water Research, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Unraveling phytoremediation mechanisms of the common reed (Phragmites australis) suspension cells towards ciprofloxacin: Xenobiotic transformation and metabolic reprogramming - Bin Wang; Hang Xu; Yu Liu; Kaiping Zhou; Xinyu Li; Deyang Kong; Jinmei Chen; Yujie He; Rong Ji (Water Research, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

Improved global estimation of seasonal variations in C3 photosynthetic capacity based on eco-evolutionary optimality hypotheses and remote sensing - Yihong Liu; Jing M. Chen; Mingzhu Xu; Rong Wang; Weiliang Fan; Wenyu Li; Lucas Kammer; Colin Prentice; Trevor F. Keenan; Nicholas G. Smith (Remote Sensing of Environment, 2024)

A novel cleaner production for ferromagnetic materials from red mud: Process design, thermodynamic study and environment assessment - Yadong Wu; Fangqi Li; Wei Liu; Chaosen Yang; Rong Liu; Hongsheng Huang (Process Safety and Environmental Protection, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Spatial and temporal dynamics of microbes and genes in drinking water reservoirs: Distribution and potential for taste and odor generation - Xuanzi Zhangsun; Honghong Guo; Quanjie Du; Na Li; Shuhong Xue; Rong Li; Wenrui Ma; Xiang Liu; Haihan Zhang; Tinglin Huang (Journal of Hazardous Materials, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Photocorrosion suppression of copper sulfide via hybridization with amino-functionalized metal–organic framework for natural sunlight-driven photocatalysis - Zewei Liu; Cheng Tang; Zepeng Yu; Shu Li; Chengzhang Deng; Sijie Liu; Zhiqiang Wu; Rong Tan (Fuel, 2024)

Novel photic responsive Janus nanoparticles: Interfacial catalysts for efficient preparation of biodiesel - Mingshu Li; Rong Zhang; Chuanxing Jia; Zhongqiu Liu; Yujing Liu; Anguo Ying (Fuel, 2024)

Investigating the temporal evolution of physicochemical attributes and flavorome profiles in Sichuan shai vinegar utilizing diverse aging techniques - Li Li; Cuixin Huang; Zhicheng Li; Yulin Zhao; Jun Liu; Yu Zheng; Rong Cao; Yuting Liao (Food Research International, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Enhanced photocatalytic hydrogen evolution via yolk–heteroshell TiO2@TiO2/SiO2 nanoreactor with confined Pt nanoparticles - Haimei Liu; Min Shi; Rong Yang; Ye Wang; Haiyan li; Qiying Su; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

Controlled assembly and synthesis of oxygen-deficient W18O49 films based on solvent molecular strategy for electrochromic energy storage smart windows - Xiaohui Sun; Wei Wu; Nana Liu; Peng Li; Xueying Zhao; Zhaozhu Qu; Kunming Zhao; Bo Wang; Xianhui Rong; Xuyang Zhang; Guohua Wu; Xiangwei Wang (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in zebrafish larvae exposed to cyclophosphamide - Tianming Liu; Dongshen Shang; Weiqi Tian; Yindong Li; Rong Xie; Jianxing Zhao; Heru Dong (Environmental Science and Pollution Research, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Effects of microplastics derived from biodegradable mulch film on different plant species growth and soil properties - Rong Liang; Chi Zhang; Ruifang Zhang; Qingyun Li; Hongquan Liu; Xin-Xin Wang (Science of The Total Environment, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Organic fertilizer substitution benefits microbial richness and wheat yield under warming - Zheng-Rong Kan; Yinan Xu; Ahmad Latif Virk; Mengting Liu; Xinyu Pei; Yanling Li; Haishui Yang; Changqing Chen (Science of The Total Environment, 2024)

Elemental and isotopic perspective on the formation of Permian mafic magmatic rocks from the Xing'an Mongolia Orogenic Belt and northern North China Craton - Wei Liu; Dongya Zou; Xiaolong Zhang; Xiaoyan Gu; Rong Xu; Gangzhu Li (Lithos, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

The impacts of cold plasma on the taste and odor formation of dried silver carp products - Yueying Zhai; Aonan Luan; Zhimeng Yang; Zhixing Rong; Yongle Liu; Faxiang Wang; Xianghong Li (Food Chemistry, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Mining of novel target genes through Pan-genome analysis for Conventional PCR and Real-Time PCR detection of Staphylococcus argenteus in food - Jiahui Huang; Jingsha Dai; Ming Liu; Shixuan Huang; Yuwei Wu; Dongli Rong; Yuanyu Li; Miao Zhao; Ying Li; Jumei Zhang; Shi Wu; Qingping Wu (Food Control, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Constructing ultralow-loading Cu single atoms/Fe2O3 particles on Nb2C MXenes for efficient utilization of atomic H to boost electrochemical debromination - Fangxian Wang; Junwei Yang; Shihao Li; Junwen Liang; Yuwei Wang; Rong Du; Bo Zhou; Qiong Liu; Changping Li (Chemical Engineering Journal, 2024)

Triarylamine-based polyimide COFs for achieving high performance ambipolar multi-color electrochromic energy-storage films - Lei Huang; Rong Guo; Qingqing Qiu; Huan Li; Putrakumar Balla; Jinming Zeng; Tongxiang Liang; Xiaopeng Qi; Ping Liu (Chemical Engineering Journal, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Tuning oxygen vacancies via photoinduced defect engineering in plasma pre-treated TiO2 for efficient solar-light-driven oxidation of trace methane - Qiyu Zhang; Jiakang Duan; Zhiping Zhu; Li Rong; Xiaochang Lin; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2024)

Three-way junction-mediated three-letter coded SDA cascade CRISPR/Cas12a system for circRNA detection - Di Wu; Xin Liu; Lujia Tang; Baiying Li; Rong Zhao; Tong Feng; Xiangyang Xiao; Guoming Xie; Wenli Feng (Chemical Engineering Journal, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

Research progress on hepatotoxicity mechanism of polygonum multiflorum and its main components - Liping Gong; Xianhui Shen; Nana Huang; Kaiyi Wu; Rongrong Li; Ying Liu; Huijie Zhang; Siyi Chen; Rong Sun (Toxicon, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Constructing direct Z-scheme heterojunction of NiCo-LDH coated with g-C3N4 for boosting photocatalytic H2 evolution - Qinyi Gu; Chujun Feng; Congtian Liu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Zhongyu Li; Song Xu (Fuel, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Enhanced reaction kinetics and structure integrity of Cu/F co-doped SnO2@C composite for high-performance lithium-ion batteries - Shixin Huang; Longjun Guo; Wei Liu; Chunjin Hang; Rong An; Yongfeng Li; Yanhong Tian (Chemical Engineering Journal, 2024)

Biokinetic and microbial insights into regulatory mechanisms of long-chain fatty acid degradation during food waste-lipid co-digestion within anaerobic membrane bioreactor - Yaqian Liu; Yu Xi; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Bioresource Technology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

In-situ construction of P-doped Ni0.5Cu0.5Co2O4 with 1D/2D hierarchical nanostructure for high-performance hybrid supercapacitors - Rong Zheng; Huiling Lu; Pengjie Zhou; Yulong Ying; Longhua Li; Yu Liu (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

The immunosuppressive landscape in tumor microenvironment - Wuyi Liu; Huyue Zhou; Wenjing Lai; Changpeng Hu; Rufu Xu; Peng Gu; Menglin Luo; Rong Zhang; Guobing Li (Immunologic Research, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Integrated Information for Pathogenicity and Treatment of Spiroplasma - Yixue You; Jianmin Xiao; Jiaxin Chen; Yuxin Li; Rong Li; Siyuan Zhang; Qichen Jiang; Peng Liu (Current Microbiology, 2024)

Harnessing key bacteria from suppressive soil to mitigate banana Panama disease - Nana Lv; Mohammadhossein Ravanbakhsh; Shuqin Ling; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Biology and Fertility of Soils, 2024)

Microneedle electrochemical sensor based on disposable stainless-steel wire for real-time analysis of indole-3-acetic acid and salicylic acid in tomato leaves infected by Pst DC3000 in situ - Lingjuan Tang; Daodong Li; Wei Liu; Yihui Tang; Rongcheng Zhang; Yiran Tian; Rong Tan; Xiaolong Yang; Lijun Sun (Analytica Chimica Acta, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

MicroRNA expression profile of chicken liver at different times after Histomonas meleagridis infection - Qiaoguang Chen; Yuming Zhang; Jie Rong; Chen Chen; Shuang Wang; Jiege Wang; Zaifan Li; Zhaofeng Hou; Dandan Liu; Jianping Tao; Jinjun Xu (Veterinary Parasitology, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Iron transformation and hydroxyl radical production during mixing surface water and groundwater in the riparian zone: Effects of bicarbonate and surface water-groundwater ratio - Shuang Li; Yao Huang; Junhao Shen; Shengjun Mao; Rong Peng; Hui Liu (Applied Geochemistry, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Mercury supply limits methylmercury production in paddy soils - Huan Zhong; Yao Su; Xinda Wu; Luís Nunes; Chengjun Li; Yunyun Hao; Yu-Rong Liu; Wenli Tang (Science of The Total Environment, 2024)

Centennial-scale cooling-induced megadroughts in Myanmar's tropical arid region over the past 8000 years - Jie Li; Jiaoyang Zhang; Jingjing Li; Miaofa Li; Jixiang Liu; Bob Hudson; Kyaing Sein; Huiling Zhang; Rong Wang; Luo Wang; Guoqiang Chu; Jule Xiao (Quaternary Science Reviews, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Long-term residue returning increased subsoil carbon quality in a rice-wheat cropping system - Yinan Xu; Yalin Yu; Jing Sheng; Yuekai Wang; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Journal of Environmental Management, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Determination of marker residues of quinoxaline-1,4-di-N-oxides and its prototype identification by liquid chromatography tandem mass spectrometry - Lu Li; Rong Liu; Longyun Liu; Zeyu Guo; Tong Zhou; Yuxi Yang; Huiping Yang; Limin He (Food Chemistry, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

Role of phytoliths in carbon stabilization of Zostera marina L. plants: One unreported mechanism of carbon sequestration in eelgrass beds - Bowen Rong; Li Zhang; Zhaojun Liu; Weihao Bai; Weidong Gu; Xiangtao Wei; Wenhao Hou; Changzi Ge (Estuarine, Coastal and Shelf Science, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Construction and applications of hybrid nanochannels with helical foldamers and solid-state nanopores - Fupeng Qin; Mengqi Sheng; Rongjie Li; Daixin Liu; Meili Ren; Rong Tian; Lyes Douadji; Deqiang Wang; Quan Gan; Liyuan Liang (Chemical Engineering Journal, 2024)

Shelterbelt effects on soil redistribution on an arable slope by wind and water - Yanru Wen; Bao Liu; Litao Lin; Mengmeng Hu; Xue Wen; Ting-Yong Li; Jiandong Rong; Shuihong Yao (CATENA, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

A nonlinear elastic-strain hardening model for frozen improved sandy soil under uniaxial compression loading condition - Bo Liu; Yanqing He; Yanhui Han; Guoxuan Wang; Rong Gao; Dongyang Li (Cold Regions Science and Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

A Novel FD3 Framework for Carbon Emissions Prediction - Houtian He; Tongyan Liu; Qianqian Li; Jiaru Yang; Rong-Long Wang; Shangce Gao (Environmental Modeling & Assessment, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

Special clinical entity with 15q26 deletion: a novel case report - Wei-Liang Liu; Fang Li; Lu Liu; Rong Ai (Journal of Genetics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

3-D imaging of whole-space environments with electromagnetic induction sensors based on linear approximation - Jintai Li; Jianxin Liu; Wenxiang Liu; Rongwen Guo; Kun Du; Rong Liu (Tunnelling and Underground Space Technology, 2024)

Corrigendum to “Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace” [Soil Dynam. Earthq. Eng. 179 (2024) 108537] - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Synergistic effects of biochar addition and filtration mode optimization on mitigating membrane fouling in high-solid anaerobic membrane bioreactors - Chengfan Jiao; Hao Chen; Yaqian Liu; Hexiang Zhao; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Science of The Total Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

Enhanced atomic H* utilization on urchin-like TiO2-supported palladium nanoparticles for efficient electrocatalytic detoxification of chlorinated organics - Jun Zhang; Shuyue Liu; Shiyu Lu; Chunyuan Wang; Pingjuan Liang; Huan Yi; Mengjie Li; Laizheng Luo; Rong Wang; Guangming Jiang (Fuel, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

PBA alleviates cadmium-induced mouse spermatogonia apoptosis by suppressing endoplasmic reticulum stress - Rong Wang; Mengyuan Li; Zhen Wu; Wenjing Gong; Mingming Zhang; Yehao Liu; Yuyou Yao; Yanli Ji (Toxicology in Vitro, 2024)

Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

Multi-source unsupervised domain adaptive mill load forecasting method based on deep learning and fusion features - Yiwen Liu; Gaowei Yan; Rong Li; Shuyi Xiao; Mifeng Ren; Lan Cheng (Minerals Engineering, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

An integrated calibration strategy for the development and validation of an LC-MS/MS method for accurate quantification of egg allergens (Gal d 1–6) in foods - Shupeng Yang; Jingjing Chen; Mohamed F. Abdallah; Haopeng Lin; Peijie Yang; Jianxun Li; Rong Zhang; Qianqian Li; Peng Lu; Shuyan Liu; Yi Li (Food Chemistry, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in female zebrafish exposed to cyclophosphamide - Tianming Liu; Heru Dong; Jianxing Zhao; Dongshen Shang; Yindong Li; Rong Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Evolution of Permeability and Gas Seepage in Deep Coal Under 3D Stress - Tenglong Rong; Pengju Liu; Jiawei Wang; Xiaojian Ren; Xianzhong Li; Guoying Wang (Natural Resources Research, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Generation of golden goldfish Carassius auratus via tyrosinase gene targeting by CRISPR/Cas9 - Huijuan Li; Xiaowen Wang; Rong Zhang; Lili Liu; Hua Zhu (Aquaculture, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Intraparticle sorption and desorption of antibiotics - Cheng Zhang; Rong Li; Dongfang Ke; Hongri Suo; Shuai Wang; Enze Ma; Yulong Chen; Chongxuan Liu (Journal of Hazardous Materials, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

Soil moisture drives the response of soil microbial nutrient limitation to N and P additions in an Inner Mongolian meadow steppe - Hong Xiao; Yuping Rong; Pengzhen Li; Yuling Liu (European Journal of Soil Biology, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Biodiversity and core microbiota of key-stone ecological clusters regulate compost maturity during cow-dung-driven composting - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Yong Yang; Xingxiang Deng; Guixian Xie; Gongwen Luo (Environmental Research, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Re-evaluating the impact of feeding shock on anaerobic co-digestion of food waste and waste activated sludge: Trade-off between efficiency and stability - Yaqian Liu; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Effects of combined exposure to polystyrene microplastics and 17α-Methyltestosterone on the reproductive system of zebrafish - Weiya Rong; Yue Chen; Zijun Xiong; Haiyan Zhao; Tongyao Li; Qing Liu; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Theriogenology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Nitrogen and phosphorus additions alter foliar nutrient concentrations of dominant grass species and regulate primary productivity in an Inner Mongolian meadow steppe - Hong Xiao; Pengzhen Li; Thomas A. Monaco; Yuling Liu; Yuping Rong (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Iridoids and other constituents from the leaves and stems of Valeriana officinalis var. latifolia - Jia-Jin Liu; Jun-Jie Hao; Min Tan; Cai-Cen Liao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

Automatic and adaptive picking of surface-wave dispersion curves for near-surface application - Hui Liu; Jing Li; Rong Hu (Journal of Applied Geophysics, 2024)

Synergistic dual-regulating the electronic structure of NiMo selenides composite for highly efficient hydrogen evolution reaction - Rong Li; Song Xie; Yujie Zeng; Qiangqiang Zhao; Minqin Mao; Zhitian Liu; Paul K. Chu; Xiang Peng (Fuel, 2024)

Experiment and dynamic simulation of hydrogen recovery from hydrogen-containing gas mixtures via hydrate-membrane coupling method - Jingbo Gao; Qiang Sun; Jia Luo; Leyan Li; Ninghui Liu; Rong Ma; Hang Zhao; Xiangming Li; Zongyu Qin; Yiwei Wang; Xuqiang Guo (Fuel, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Fifty-year pollution history of microplastics and influencing factors in offshore sediments: A case study of Ningbo, China - Zhenhong Zhu; Xuexi Xiao; Rong Wu; Chong Jin; Tong Li; Weiping Liu (Environmental Pollution, 2024)

Reliability-based design optimization scheme of isolation capacity of nonlinear vibration isolators - Huizhen Liu; Xianzhen Huang; Zhiyuan Jiang; Shangjie Li; Zhiming Rong (Engineering Structures, 2024)

Negative thermopower anisotropic ionic thermoelectric hydrogels based on synergistic coordination and hydration for low-grade heat harvesting - Luzheng Chen; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Wenjia Han; Jiang Lou (Chemical Engineering Journal, 2024)

Reactant enrichment in yolk-shell structured Pd/TiN nanoreactors for boosting electrocatalytic hydrodechlorination performance - Jun Zhang; Chunyuan Wang; Shiyu Lu; Shuyue Liu; Pingjuan Liang; Huan Yi; Mengjie Li; Meng Jin; Rong Wang; Guangming Jiang (Chemical Engineering Journal, 2024)

Intercropping with Trifolium repens contributes disease suppression of banana Fusarium wilt by reshaping soil protistan communities - Xiangyu Ren; Zeyuan Zhou; Manyi Liu; Zongzhuan Shen; Beibei Wang; Alexandre Jousset; Stefan Geisen; Mohammadhossein Ravanbakhsh; George A. Kowalchuk; Rong Li; Qirong Shen; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Disclosing phototransformation mechanisms of decabromodiphenyl ether (BDE-209) in different media by simulated sunlight: Implication by compound-specific stable isotope analysis - Guoguang Wang; Chuanyuan Li; Shuaihao Liu; Ziao Xing; Pengxu Guo; Zixuan Hao; Maojiao Li; Haixia Wang; Guangzhi Rong; Yu Liu (Environmental Science and Pollution Research, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Unraveling the role of Financial Risk, social globalization and Economic Risk towards attaining sustainable environment in China: Does resources curse still holds - Liu Rong; Zhenbo Wang; Zhijun Li (Resources Policy, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Iron isotope evidence in continental intraplate basalts for mantle lithosphere imprint on heterogenous asthenospheric melts - Rong Xu; Sarah Lambart; Oliver Nebel; Ming Li; Zhongjie Bai; Junbo Zhang; Ganglan Zhang; Jianfeng Gao; Hong Zhong; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Multiscale computational fluid dynamics modelling of spatial ALD on porous li-ion battery electrodes - Zoushuang Li; Yuanxiao Chen; Yufeng Nie; Fan Yang; Xiao Liu; Yuan Gao; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

HIF-1α: A potential therapeutic opportunity in renal fibrosis - Disheng Liu; Lu Wang; Wuhua Ha; Kan Li; Rong Shen; Degui Wang (Chemico-Biological Interactions, 2024)

RETRACTED ARTICLE: Liquiritin reduces ferroptosis in doxorubicin-induced cardiotoxicity through targeting SLC7A11/GPX4 pathway - Mei Wang; Meng Liu; Lijing Tang; Lixian Shen; Junhui Xiao; Rong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)